2020
DOI: 10.1093/jxb/eraa381
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging reveals convergence in root and stem vulnerability to cavitation across five tree species

Abstract: Root vulnerability to cavitation is challenging to measure and under-represented in current datasets. This gap limits the precision of models used to predict plant responses to drought because roots comprise the critical interface between plant and soil. In this study we measured vulnerability to drought induced cavitation in woody roots and stems of five tree species (Acacia aneura, Cedrus deodara, Eucalyptus crebra, Eucalytus saligna, and Quercus palustris) with a wide range of xylem anatomies. X-ray microto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 80 publications
(138 reference statements)
0
18
0
Order By: Relevance
“…The strong correlation between PLV and PLC is supported by numerous studies (Gauthey et al, 2020; Li et al, 2020; Peters et al, 2020) which suggests that loss of conductivity in this species can be approximated by counting gas filled vessels, especially if vessel diameter remains relatively constant within the stem.…”
Section: Methodsmentioning
confidence: 64%
“…The strong correlation between PLV and PLC is supported by numerous studies (Gauthey et al, 2020; Li et al, 2020; Peters et al, 2020) which suggests that loss of conductivity in this species can be approximated by counting gas filled vessels, especially if vessel diameter remains relatively constant within the stem.…”
Section: Methodsmentioning
confidence: 64%
“…This assumption is supported by some early studies showing that roots are often more vulnerable to embolism than stems or leaves ( Johnson et al, 2016 ; Wason et al, 2018 ). However, some recent findings suggest that roots are comparably or even more tolerant to drought-induced embolism compared with other organs in some species ( Rodriguez-Dominguez et al, 2018 ; Peters et al, 2020 ; Lübbe et al, 2021 ). Clearly, more studies are required to confirm the spatial pattern of vulnerability to embolism within plants, particularly within the root system and rhizosphere.…”
Section: Parameterizing Drought-induced Hydraulic Failure: What Trait...mentioning
confidence: 99%
“…In line with this main result, a growing number of recent studies using different techniques have confirmed that roots are notably more embolism resistant than previously thought. These studies used the micro‐CT technique and the optical method, both direct and non‐invasive methods applied on intact plants (Losso et al., 2019; Peters et al, 2020; Rodriguez‐Dominguez et al., 2018; Skelton et al., 2017), the rehydration kinetics technique (Creek et al., 2018), the single‐vessel air‐injection method (Wason et al., 2018) and the pneumatic method (Wu et al., 2020). Together with our study, the results from six independent methods are largely in contradiction with the majority of former comparative studies, which found the root xylem to be the most vulnerable organ along the hydraulic pathway in a wide range of species from different environments (e.g.…”
Section: Discussionmentioning
confidence: 99%